Molecular Detection of Anaplasma phagocytophilum in Cats in Europe and Associated Risk Factors - Vera Geisen; Nikola Pantchev; Yury Zablotski; Olga Kim; Majda Globokar Vrhovec; Katrin Hartmann; Michéle Bergmann (Animals, 2024)
Infections with Anaplasma (A.) phagocytophilum in cats seem to be rare. The study aimed to determine whether infections in cats are underestimated and to identify the risk factors for infection. Blood samples of 1015 cats across Europe (2017–2022), sent to IDEXX Laboratories, Germany, were tested for A. phagocytophilum DNA. The influence of the cats’ origin on A. phagocytophilum infection was assessed by univariable analysis, while multivariable logistic regression evaluated associations with the cats’ sex and age, and the years, and seasonality of the samples’ submission. Furthermore, univariable linear regression was used to determine patterns in PCR orders. The number of submitted samples increased significantly during the 6 years (p = 0.042). Anaplasma phagocytophilum DNA was detected in 76/1015 of cats (7.5%, 95% CI 6.0–9.3%). Infections were significantly more common in Northern compared to Central (p < 0.001, OR: 8.70) and Southern Europe (p < 0.001, OR: 39.94). A significantly higher likelihood for infections during the summer compared with winter (p = 0.047, OR: 3.13) was found. Bacteremia with A. phagocytophilum in European cats is not uncommon. Anaplasma phagocytophilum infection should be considered an important risk, particularly in Northern Europe. Effective tick prevention is crucial for managing feline health across Europe, not just in the Mediterranean region.